2020
DOI: 10.18632/aging.202144
|View full text |Cite
|
Sign up to set email alerts
|

DOK3 is involved in microglial cell activation in neuropathic pain by interacting with GPR84

Abstract: Adaptor molecule downstream of kinase-3 (DOK3) is a vital regulator of innate immune responses in macrophages and B cells, and G-protein-coupled receptor 84 (GPR84) is significant in mediating the biosynthesis and maintenance of inflammatory mediators that are induced by neuropathic pain in microglia. In the present study, we determined the role of DOK3 in activating microglia-induced neuropathic pain and investigated the underlying mechanisms associated with GPR84. We found that knockdown of DOK3 in microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Then, tumor samples were classi ed according to different immune subtypes of C1-C6 ( 9), and the expression levels of DOK1-DOK7 RNA-seq were statistically analyzed, and the results showed that these genes were signi cantly correlated with the immunotyping. As previously reported, DOK3 is an important modulator of innate immune responses in macrophages and B cells and modulates downstream signaling pathways of various immune receptors (22,23). DOK1 is a tumor suppressor that is often lost in malignant cells, but it still regulates the immunoreceptor activity of stromal cells in the tumor microenvironment and promotes the invasion of cancer cells (24,25).…”
Section: Discussionmentioning
confidence: 80%
“…Then, tumor samples were classi ed according to different immune subtypes of C1-C6 ( 9), and the expression levels of DOK1-DOK7 RNA-seq were statistically analyzed, and the results showed that these genes were signi cantly correlated with the immunotyping. As previously reported, DOK3 is an important modulator of innate immune responses in macrophages and B cells and modulates downstream signaling pathways of various immune receptors (22,23). DOK1 is a tumor suppressor that is often lost in malignant cells, but it still regulates the immunoreceptor activity of stromal cells in the tumor microenvironment and promotes the invasion of cancer cells (24,25).…”
Section: Discussionmentioning
confidence: 80%
“…In the central nervous system, microglia monitor the local environment to respond quickly to a wide range of inflammatory stimuli, while astrocytes function as immune response cells to produce a large number of inflammatory mediators [ 6 , 33 ]. To evaluate the effects of RIP3 and JNK inhibitors on the density of glial cells and the activation of microglia and astrocytes in vivo , we stained for the astrocyte-specific marker glial fibrillary acidic protein (GFAP) and the microglia- specific marker ionized calcium-binding adaptor molecule 1 (IBA-1).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, HCK is a hematopoietic cell kinase whose dysregulation may affect microglia (i.e., resident immune cells in the central nervous system playing critical roles in brain immunity, development, and homeostasis) and accelerate early stage Alzheimer's disease-like neuropathology 46 . Recently, also the colony stimulating factor 3 receptor (CSF3R) and the docking protein 3 (DOK3) was found to be involved in the in microglial cell activation 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%